1982
DOI: 10.1677/joe.0.0940429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pancreatectomy, tolbutamide and insulin on glucose fluxes in chickens

Abstract: The effects of pancreatectomy and of injection of insulin or Tolbutamide on glucose fluxes in chickens were examined. This was prompted by earlier observations that Tolbutamide seems not to require the presence of pancreatic insulin for its acute hypoglycaemic action in this species. Rates of appearance (Ra) and disappearance (Rd) of glucose were estimated by isotope dilution using [14C]glucose in single-injection experiments and [14C]glucose and [6-3H]glucose in priming-injection + constant-infusion experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…The prolonged hypoglycemic state from 4 h PI to 36 h PI after a single injection of tolbutamide, associated with a profound rise in plasma insulin concentrations at 0.5 h PI, is in agreement with in vitro and in vivo studies on layer and broiler chickens at different ages [9,[14][15][16][17][18][25][26][27][28] and with in vitro and in vivo studies on mice, rats, dogs, and hamsters [29][30][31][32][33]. Indeed, tolbutamide is a potent hypoglycemic agent in mammals and birds and stimulates insulin secretion from pancreatic b-cells, principally by inhibiting adenosine triphosphatesensitive K þ channels in the cell membrane, consequently, causing a membrane depolarization and an activation of voltage-gated Ca 2þ influx [34][35][36].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The prolonged hypoglycemic state from 4 h PI to 36 h PI after a single injection of tolbutamide, associated with a profound rise in plasma insulin concentrations at 0.5 h PI, is in agreement with in vitro and in vivo studies on layer and broiler chickens at different ages [9,[14][15][16][17][18][25][26][27][28] and with in vitro and in vivo studies on mice, rats, dogs, and hamsters [29][30][31][32][33]. Indeed, tolbutamide is a potent hypoglycemic agent in mammals and birds and stimulates insulin secretion from pancreatic b-cells, principally by inhibiting adenosine triphosphatesensitive K þ channels in the cell membrane, consequently, causing a membrane depolarization and an activation of voltage-gated Ca 2þ influx [34][35][36].…”
Section: Discussionsupporting
confidence: 86%
“…Tolbutamide activates glycolytic and glycogenic pathways and inhibits gluconeogenic pathway through regulating key enzyme activities in the liver [38]. Danby et al [17] demonstrated that in pancreatectomized chickens, the hypoglycemic action of tolbutamide depends on an inhibition of glucose release by the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we investigated only lactate as a glucose precursor, a mechanism for action for tolazamide similar to that for glisoxepide may exist. Also, in pancreatectomized chickens, tolbutamide was capable of attenuating hepatic glucose production, most likely by affecting gluconeogenesis (27). However, other studies can be found in which an insulin-independent sulfonyl-1272 EFFECT OF TOLAZAMIDE ON LIVER Endo • 1986 Volll9«No3 urea effect on hepatic gluconeogenesis was not apparent.…”
Section: Discussionmentioning
confidence: 96%